2018
DOI: 10.1021/acsinfecdis.8b00026
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Warfare at the Microorganismal Level: A Closer Look at the Superoxide Dismutase Enzymes of Pathogens

Abstract: Superoxide anion radical is generated as a natural byproduct of aerobic metabolism, but is also produced as part of the oxidative burst of the innate immune response design to kill pathogens. In living systems, superoxide is largely managed through superoxide dismutases (SODs), families of metalloenzymes that use Fe, Mn, Ni or Cu cofactors to catalyze the disproportionation of superoxide to oxygen and hydrogen peroxide. Given the bursts of superoxide faced by microbial pathogens, it comes as no surprise that S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 171 publications
(384 reference statements)
1
26
0
Order By: Relevance
“…The enhanced SOD activity in the presence of the metal ions suggests the production of ROS. Moreover, the boosting of SOD activity in P. sativum might be attributed to the de novo synthesis of enzyme protein by the transcription of SOD genes through a superoxide-mediated transduction signal [36]. The present results show that the enhancement of SOD activity is in parallel with H 2 O 2 production in plant cells (Figure 1c or Figure 3b).…”
Section: Discussionsupporting
confidence: 53%
“…The enhanced SOD activity in the presence of the metal ions suggests the production of ROS. Moreover, the boosting of SOD activity in P. sativum might be attributed to the de novo synthesis of enzyme protein by the transcription of SOD genes through a superoxide-mediated transduction signal [36]. The present results show that the enhancement of SOD activity is in parallel with H 2 O 2 production in plant cells (Figure 1c or Figure 3b).…”
Section: Discussionsupporting
confidence: 53%
“…Moreover, reproductive systems depend on ROS to facilitate fertilization and normal maturation [15][16][17] (Figure 2). In addition, ROS are important during host defenses, directly and indirectly contributing to the destruction of microorganisms [18][19][20][21][22] (Figure 2). Thus, the key roles of ROS in biological processes are cell signaling, biosynthetic processes, and host defense.…”
Section: Physiological Roles Of Rosmentioning
confidence: 99%
“…We also investigated the impact of ROS by expressing the heme sensor in deletion mutants lacking either the cytosolic superoxide dismutase (strain sod1 Δ hs ) or the mitochondrial superoxide dismutase (strain sod2 Δ hs ). Superoxide dismutases, as well as other antioxidant proteins (e.g., catalases, glutathione peroxidases, and peroxiredoxins), protect cellular components from ROS damage ( 61 , 62 ). We found that the sod1 Δ hs strain showed similar eGFP/mKATE2 fluorescence ratios to those of WT hs when exposed to hemin, and the sod2 Δ hs strain exhibited a reduction in the sensor response under the same conditions ( Fig.…”
Section: Resultsmentioning
confidence: 99%